Implementasi Sistem Operasional & Analisis Visitor - Izza Rizwaan, Fadzle; Asmar Musa, Andi; Haryono, Wasis (Shofanah Media Berkah, 2025)
Prime Gears Bintaro is a motorcycle apparel retail store that still uses manual systems to record visitor data and perform helmet fitting processes. This system has led to various issues, such as low operational efficiency, a high potential for data errors, and limitations in data-driven decision-making. This study aims to design and develop a digital operational system capable of recording visitor data and providing an automatic and accurate helmet size recommendation feature. The methodology used is qualitative, including direct observation of store operations, interviews with relevant personnel, and literature review to strengthen the theoretical and technological foundation. The results of this study show that the developed system improves store operational efficiency, speeds up customer service processes, and assists management in analyzing consumer behavior and identifying fast-moving and slow-moving products. Thus, the system is expected to enhance service quality and support strategic decision-making in the motorcycle apparel retail environment.